2021
DOI: 10.1111/acps.13309
|View full text |Cite
|
Sign up to set email alerts
|

Severe mental illness is associated with increased mortality and severe course of COVID‐19

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research.-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 36 publications
0
73
2
Order By: Relevance
“…Overall, these results emphasize the importance of addressing the increased physical health risk profile in patients with BD. This is underlined by the results from a recent Danish register study showing that patients with BD, who had a positive COVID-19 test, had a more unfavorable physical illness outcome in comparison to patients with COVID-19 not having a severe mental illness ( 27 ). The present findings support the described recommendations made by Hernández-Gómez et al ( 1 ) and underline that patients with BD should be considered as an at-risk population, presumably, especially vulnerable to relapse during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these results emphasize the importance of addressing the increased physical health risk profile in patients with BD. This is underlined by the results from a recent Danish register study showing that patients with BD, who had a positive COVID-19 test, had a more unfavorable physical illness outcome in comparison to patients with COVID-19 not having a severe mental illness ( 27 ). The present findings support the described recommendations made by Hernández-Gómez et al ( 1 ) and underline that patients with BD should be considered as an at-risk population, presumably, especially vulnerable to relapse during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals in Denmark who tested positive for SARS-CoV-2 were found to have a much higher chance of dying and experiencing severe COVID-19 if they were previously diagnosed with a schizophrenia spectrum, bipolar disorder, or unipolar depression or filled a prescription for psychotropic drugs than individuals without psychiatric disorders [ 148 ]. Additionally, a study in Sweden found that individuals with severe mental disorders (e.g., psychotic and bipolar disorders) were almost twice as likely to experience a COVID-19 associated death, and these odds increased to four fold for individuals with severe mental disorders between the ages of 60 and 79 years old [ 149 ].…”
Section: Neuropsychiatric Disorders and Vulnerability To Covid-19mentioning
confidence: 99%
“…In a recent study, the prevalence of schizophrenia was 3.6% in 7,341 patients with COVID-19, much higher than the 0.66% prevalence in the general population (11)(12)(13). Previous studies have shown that people with mental illness are two to seven times more likely to die after a respiratory infection, and severe mental health disorders have been shown to be a risk factor for increased mortality from COVID-19 (13)(14)(15). Furthermore, extensive studies indicate that while COVID-19 is damaging to the respiratory system, it can also have negative mental health effects.…”
Section: Introductionmentioning
confidence: 96%
“…COVID-19 is caused by SARS-CoV-2, which belongs to the coronavirus family (15,18). Its pathogenicity is effected via the angiotensin-converting enzyme-2 receptor (ACE2) (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%